Biosecurity, economic collapse, the state to come: political power in the pandemic and beyond - Boukalas, Christos (Directions and developments in criminal justice and law, 2023)
"What kind of state emerges from the pandemic? The pandemic caused two crises, in biosecurity and in the economy. The state was forced to tackle both; but subduing one inevitably exacerbated the other. Emerging from the impossible task of handling two conflicting crises is a new form of state, the state to come. To outline the emerging state, this book offers an in-depth critical account of the state's responses to the biosecurity and the economic crises. It is thus the first study to address both crises ensuing from the pandemic, and to synthesise the responses to them in a comprehensive account of political power. Addressing biosecurity, the book deciphers its key modalities, epistemic premises, its law, the threat it aims to oppose, and the ways in which it relates to public health and society -especially its extraordinary power to suspend society. Addressing the economic crisis, the book deciphers the actuality and prospects of both the economy and the state's economic policy. It claims that economic policy is now dual: it adopts countercyclical measures to serve and entrench a neoliberal economy. The responses to the twin crises inform the outline of the emerging state: its structure, logic, and legality; its power and its relation to society. This is a state of extraordinary power; but its only purpose is to preserve the social order intact. It is a despotic state: powerful, and set to impose social stasis. This book offers groundbreaking analysis based on our pandemic experience. It is indispensable for critical scholars and students in Politics, Security Studies, Sociology, Law, Political Economy and Public Health"--